ChemInform Abstract: Product Control in Alkene Trifluoromethylation: Hydrotrifluoromethylation, Vinylic Trifluoromethylation, and Iodotrifluoromethylation Using Togni Reagent. Issue 6 (21st January 2016) - Egami, Hiromichi; Usui, Yoshihiko; Kawamura, Shintaro; Nagashima, Sayoko; Sodeoka, Mikiko
Abstract: Three distinct products, e.